Two Late Pleistocene climate-driven incision/aggradation rhythms in the middle Dnieper River basin, west-central Russian Plain. (15th June 2017) - Panin, Andrei; Adamiec, Grzegorz; Buylaert, Jan-Pieter; Matlakhova, Ekaterina; Moska, Piotr; Novenko, Elena
Abstract: In valleys of the River Seim and its tributaries in the middle Dnieper basin (west-central Russian Plain), two low terraces (T1, 10–16 m, and T0, 5–7 m above the river) and a floodplain (2–4 m) with characteristic large and small palaeochannels exist. A range of field and laboratory techniques was applied and ∼30 new numerical ages (OSL and 14C dates) were obtained to establish a chronology of incision and aggradation events that resulted in the current valley morphology. Two full incision/aggradation rhythms and one additional aggradation phase from the previous rhythm were recognized in the Late Pleistocene – Holocene climate cycle. The following events were detected. (1) Late MIS 5 – early MIS 4: aggradation of Terrace T1 following the deep incision at the end of MIS 6. (2) Late MIS 4 (40–30 ka): incision into Terrace T1 below the present-day river, formation of the main scarp in the bottom of the valley between Terrace T1 and Terrace T0/Floodplain levels. (3) MIS 2: aggradation of Terrace T0, lateral migrations of a shallow braided channel located few meters above the present-day river since ∼25 ka through the LGM. (4) 18–13 ka: incision into Terrace T0 below the modern river. Multiple-thread channels concentrated in a single flow that at some places formed large meanders. In the period 15–13 ka, high floods that rose above the present-day floods left large levees and overbank loams on Terrace T0. (5) Younger Dryas – Holocene transition: aggradation up to the modern channel level, transformation of large Late Glacial to small Holocene meanders. The established incision/aggradation rhythms are believed to be manifested over the Central Russian Plain outside the influence of ice sheets in the north and base level changes in the south. The two-phase deepening of the valley occurred in the last quarter of the last glacial epoch but can not be attributed directly to the glacial-interglacial transition. Both the detected incision events correspond to relatively warm climate phases – late MIS 3, post-LGM warming including the Bølling-Allerød interstadial. Anomalously large size of the preserved river palaeochannels prove that the post-LGM incision phase was induced by a climatically forced large increase of water runoff. Considerable increase of water discharges is considered the most probably cause for the late MIS 4 incision phase also. Therefore river incision seems to have been governed rather by changing water runoff that oscillated in phase shift with the thermal regime. Highlights: General valley incision was not directly at the glacial-interglacial transition. Incision occurred during interstadial climate phases in the end of the last glacial. Both incision events were governed by climatically driven increase of water runoff. Pleistocene – Holocene transition was characterized by valley aggradation. The LGM river terrace is similar in elevation to the Holocene floodplain.